Cultural Reserve of "Siak" Dutch Prison As a Learning Resources of Local History - Pernantah, Piki Setri; Sholeha, Iis; Amanda, Lionita; Rizka, Adelia; Pangabean, Angelica Putri; Sakilah, Sakilah (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
The State Palace of Siak Sri Indrapura, indeed has a lot of priceless cultural heritage objects as a reflection of the glorious history of Malay in the past. In addition to palace relics, there are other historical sites that have no less high historical value, such as the Syahbuddin Mosque, the Tomb of King Kecik, and the Dutch Barracks and many others. The Dutch colonial in historical records as one of the western nations that colonized Indonesia for quite a long time. It is undeniable that the Malay kingdom centered in Siak Sri Indrapura was also the territory of the Dutch at that time. Evidence of the position of the Dutch in the Malay Archipelago is the establishment of a Dutch military barracks located on Jalan Benteng Hulu, Mempura District, Siak Regency. The location of this Dutch barracks is right across from the center of the Siak Sri Indrapura Kingdom which is only separated by the Siak river. Prison is a term for a Dutch building complex whose function was as a place of protection and defense for the Dutch army. In the barracks there are several types of buildings consisting of dormitories, offices, armory, logistics and prisons. Inside the barracks there is also a prison with a size of 2-3 meters with a capacity of 4-8 people, to detain Indigenous people, especially the people of Siak who are against and disobedient to the Dutch Colonial. Now the Dutch prison not only functions as a cultural heritage but is also transformed into a beautiful tourist destination. Concerns began to arise, that in the future the community would only regard the Dutch barracks building as a mere symbol, without trying harder to be curious and learn more about the history behind the establishment of the building. Based on this, the authors are interested in this research as a learning resource of Local History with literacy study and data collection techniques used are observation, literature study and documentation through data analysis based on analysis and comparison of various existing data.